Optimasi biaya dalam proses pemurnian metanol untuk mengurangi resin sebagai limbah bahan berbahaya dan beracun di PT Kaltim Methanol Industri - Reno Imam Arthapersada; Muhammad Kurniawan Adiputra; Indra P. Hakim; Imam Karfendi Putro; Asep Zainuddin; Lisendra Marbelia; Ahmad T. Yuliansyah (Jurnal Rekayasa Proses, 2020)
Purification process of raw methanol from its impurities to produce pure methanol at PT. Kaltim Methanol Industri (PT KMI) is carried out by several steps, including degassing, distillation, and adsorption. One of the impurities, tri methyl amine (TMA), could be removed by adding NaOH. Another method to remove TMA is conducted by adsorption process on ion exchange resin on the vessel called TMA catchpot. The TMA catchpot performance is very crucial in methanol purification process. Thus, monitoring and optimization are required to be performed regularly. Once the TMA catchpot resin has exhausted, the performance will be drop and methanol purification could not be done efficiently. Furthermore, the ion exchange resin should be replaced with new resin. This study evaluates the performance of the TMA catchpot during the charge of 2010, 2012, and 2016, calculates the NaOH consumption during operational time, and optimizes the cost. Resin regeneration option was introduced and compared with the conventional method (i.e. resin replacement). Economic evaluation shows that the lowest annual cost could be obtained by fresh resin replacement every 4 years and resin regeneration every 2 years. Resin regeneration option gives not only annual cost reduction, but also positive impact to the environment, by decreasing the amount of hazardous waste (i.e. spent resin) significantly.